Brain blood and cerebrospinal fluid flow dynamics during rhythmic handgrip exercise in young healthy men and women. (16th February 2021) - Tarumi, Takashi; Yamabe, Takayuki; Fukuie, Marina; Zhu, David C.; Zhang, Rong; Ogoh, Shigehiko; Sugawara, Jun
Abstract : Key points: The cerebral fluid response to exercise, including the arterial and venous cerebral blood flow (CBF) and cerebrospinal fluid (CSF), currently remains unknown. We used time‐resolved phase‐contrast magnetic resonance imaging to assess changes in CBF and CSF flow dynamics during moderate‐intensity rhythmic handgrip (RHG) exercise in young healthy men and women. Our data demonstrated that RHG increases the cerebral arterial inflow and venous outflow while decreasing the pulsatile CSF flow during RHG. Furthermore, changes in blood stroke volume at the measured arteries, veins, and sinuses and CSF stroke volume at the cerebral aqueduct were positively correlated with each other during RHG. Male and female participants exhibited distinct blood pressure responses to RHG, but their cerebral fluid responses were similar. These results collectively suggest that RHG influences both CBF and CSF flow dynamics in a way that is consistent with the Monro–Kellie hypothesis to maintain intracranial volume‐pressure homeostasis in young healthy adults. Abstract: Cerebral blood flow (CBF) increases during exercise, but its impact on cerebrospinal fluid (CSF) flow remains unknown. This study investigated CBF and CSF flow dynamics during moderate‐intensity rhythmic handgrip (RHG) exercise in young healthy men and women. Twenty‐six participants (12 women) underwent the RHG and resting control conditions in random order. Participants performed 3 sets of RHG, during which cine phase‐contrast magnetic resonance imaging (PC‐MRI) was performed to measure blood stroke volume (SV) and flow rate in the internal carotid (ICA) and vertebral (VA) arteries, the internal jugular vein (IJV), the superior sagittal (SSS) and straight sinuses (SRS), and CSF SV and flow rate in the cerebral aqueduct of Sylvius. Blood pressure, end‐tidal CO2 (EtCO2 ), heart rate (HR), and respiratory rate were simultaneously measured during cine PC‐MRI scans. Compared with control conditions, RHG showed significant elevations of HR, mean arterial pressure, and respiratory rate with a mild reduction of EtCO2 (all P < 0.05). RHG decreased blood SV in the measured arteries, veins, and sinuses and CSF SV in the aqueduct (all P < 0.05). Conversely, RHG increased blood flow in the ICA, VA, and IJV (all P < 0.05). At the aqueduct, RHG decreased the absolute CSF flow rate ( P = 0.0307), which was calculated as a sum of the caudal and cranial CSF flow rates. Change in the ICA SV was positively correlated with changes in the IJV, SSS, SRS, and aqueductal SV during RHG (all P < 0.05). These findings demonstrate a close coupling between the CBF and CSF flow dynamics during RHG in young healthy adults. Key points: The cerebral fluid response to exercise, including the arterial and venous cerebral blood flow (CBF) and cerebrospinal fluid (CSF), currently remains unknown. We used time‐resolved phase‐contrast magnetic resonance imaging to assess changes in CBF and CSF flow dynamics during moderate‐intensity rhythmic handgrip (RHG) exercise in young healthy men and women. Our data demonstrated that RHG increases the cerebral arterial inflow and venous outflow while decreasing the pulsatile CSF flow during RHG. Furthermore, changes in blood stroke volume at the measured arteries, veins, and sinuses and CSF stroke volume at the cerebral aqueduct were positively correlated with each other during RHG. Male and female participants exhibited distinct blood pressure responses to RHG, but their cerebral fluid responses were similar. These results collectively suggest that RHG influences both CBF and CSF flow dynamics in a way that is consistent with the Monro–Kellie hypothesis to maintain intracranial volume‐pressure homeostasis in young healthy adults.